EVALUASI PERTUMBUHAN BENIH PATIN (Pangasius hypophthalmus) YANG DIBERI PAKAN TAMBAHAN CACING SUTRA (Tubifex sp.) - Islama, Dini; Najmi, Nurul (Universitas Teuku Umar, 2019)
This study aimed to evaluate of patin seed (Pangasius hypothalamus) that is given Tubifex sp. as additional feed. The experiment design was used completely randomized design with four treatments and four replications. The treatments studied were 100 % pellet without the addition of Tubifex sp. (A), 95 % pellet with the addition of Tubifex sp. 5 % (B), 90 % pellet with the addition of Tubifex sp. 10 % (C) and 85 % pellet with the addition of Tubifex sp. 15 % (D). Patin seed stocking density was 1 individu/l with the length of 3-4 cm and weight of 0,15-0,28 g. The culture period for one cycle of fish farming was 40 days. The ANOVA test showed commercial feeding with the addition of Tubifex sp. as additional feed gave the significant effect on the specific of growth rate, length and feed conversion ratio, but did not give the significant effect on survival rate of patin seed. The best dose to increase the growth of catfish seeds is 85% commercial feeding with the addition of Tubifex sp. 15%.